THE CONCEPT OF "INDEPENDENT WORK OF STUDENTS" IN MODERN DIDACTICS - Olimova Guli Olimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Establishing a relationship between the concepts of "independence" and "independent work" allows us to conclude that independence is one of the leading personality traits, expressed in the ability to set certain goals, to achieve them on their own ability to change the algorithm of their actions depending on changing conditions. Independence means a person's responsible attitude to his actions. The ability to act consciously in any conditions, make unconventional decisions, being a leader and organizer.